2022
DOI: 10.1002/cssc.202102350
|View full text |Cite
|
Sign up to set email alerts
|

A Thin In2S3 Interfacial Layer for Reducing Defects and Roughness of Cu2ZnSn(S,Se)4 Thin‐Film Solar Cells

Abstract: Cu 2 ZnSn(S,Se) 4 (CZTSSe) has generated considerable research interest owing to its composition of abundant elements and excellent light-absorption properties. However, CZTSSe thin-film solar cells suffer from a considerable deficit in the open-circuit voltage (V OC ), which is mainly due to the severe interfacial recombination induced by the rough surface of CZTSSe and numerous physical defects. In this study, to improve the morphology and reduce the interfacial recombination, an In 2 S 3 passivation layer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Transient photovoltage decay (TPVD) analysis reveals that the device with 15% urea showed a longer minority carrier lifetime (Figure E), indicating a reduced nonradiative recombination due to the defect passivation . The temperature dependency of V oc (Figure F) also shows that the difference between the activation energy of the dominant recombination process ( E A ) and E g in the device with the urea additive (0.06 eV) is smaller than that without the urea additive (0.27 eV), indicating the excellent defect passivation capability of the urea additive. , …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Transient photovoltage decay (TPVD) analysis reveals that the device with 15% urea showed a longer minority carrier lifetime (Figure E), indicating a reduced nonradiative recombination due to the defect passivation . The temperature dependency of V oc (Figure F) also shows that the difference between the activation energy of the dominant recombination process ( E A ) and E g in the device with the urea additive (0.06 eV) is smaller than that without the urea additive (0.27 eV), indicating the excellent defect passivation capability of the urea additive. , …”
mentioning
confidence: 93%
“…35 The temperature dependency of V oc (Figure 2F) also shows that the difference between the activation energy of the dominant recombination process (E A ) and E g in the device with the urea additive (0.06 eV) is smaller than that without the urea additive (0.27 eV), indicating the excellent defect passivation capability of the urea additive. 36,37 Before the fabrication of 3J devices, 2J tandem devices were fabricated by directly preparing a 1.96 eV PSC on a transparent 1.56 eV PSC without any ALD layer, for which the optimal composition of the ACN/MA volatile solvent was used (Figure S11). The 2J device exhibits a PCE of 15.35% with J sc , V oc , and FF of 10.79 mA/cm 2 , 2.1 V, and 67.7%, respectively (Figure 3A), indicating no degradation of the underneath subcell.…”
mentioning
confidence: 99%
“…Moreover, a dense CSTSSe surface can combine with the CdS buffer layer to form a PN junction with good properties. 35 As a result, both the open-circuit voltage ( V oc ) and short-circuit current density ( J sc ) would be improved. 36…”
Section: Resultsmentioning
confidence: 99%
“…, TiO 2 , 110 SnO 2 , 111 Al 2 O 3 , 98–100 and In 2 S 3 (ref. 112)) have been developed as passivation layers for CZTSSe. 33 The primary role of most passivation layers is to passivate the interface defects and optimize the band alignment and thus reduce the interface recombination.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…Recently, an In 2 S 3 passivation layer was used with the CZTSSe/CdS interface to improve the front interface roughness and reduce interfacial recombination, and it was demonstrated that this method could effectively control the surface morphology and defect density of CZTSSe thin-film solar cells. 112 The presence of the In 2 S 3 layer led to an homogeneous growth of CdS without macroscopic CdS agglomeration ( i.e. , a reduced roughness of the full device), thereby improving the quality of the heterojunction (as shown in Fig.…”
Section: Interface Engineeringmentioning
confidence: 99%